DESIGN OF AN ARTIFICIAL INTELLIGENCE-BASED NON-LINEAR CONTROLLER OF A 3-DOF QUARTER ACTIVE VEHICLE SUSPENSION SYSTEM USING AN ELECTRO-HYDRAULIC - Manahil Iqra; Ali Murtaza; Muhammad Iftikhar Khan; Shaukat Ali Shah; Muhammad Waqas; Bilal Ahmed; Haroon Shams (Spectrum of Engineering Sciences, 2025)
A vehicle usually encounters road disturbances and an active vehicle suspension system is used to minimize the impact of these road disturbances to ensure a comfortable ride. Vehicles usually comes in contact with sudden road disturbances, such as depression, bumps, acceleration and deceleration, etc and this could lead to an uncomfortable ride and road accidents. So, in this work, a three degree of freedom quarter active vehicular suspension system is modelled and an electro-hydraulic actuator is also modeled for this system. Then an Artificial Intelligence (AI) based non-linear controller is designed for this system, due to which the system becomes more stable, robust and minimizes the uncertainty in the system. A simulation model has been created using MATLAB/Simulink to analyze the impact of road disturbances on a vehicle's suspension system. The results are verified for two different road cases such as no-off-roading case and off-roading case at different speeds and these results shows that the active suspension system model is stable than passive suspension system as the controller is used to improve the system response by stabilizing overshoot, undershoot and settling time of the system.